Analyzing factors that influence syariah commercial bank financial performance in indonesia based on syariah Enterprise theory (set) perspective - Fitriani, Ajeng Pipit; ,, Sutrisno; Rahman, Aulia Fuad (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2018)
This research purpose is to test empirically and analyze the influence of zakat, qardh, murabahah, mudharabah, musyarakah, and corporate social responsibility (CSR) towards financial performance (ROA) Commercial Bank Syariah in Indonesia in 2012-2016 period of time. The analyzing technique used double linear regression. Research population is Syariah Commercial Bank listed in Financial Service Authority (in Indonesia called OJK) year 2012-2016. The sample taken by using purposive sampling, within the Syariah Commercial Bank criteria that showed the financial report in 2012-2016 period. The data taken based on publication that conducted by the enlisted Banks. Thus, the number of taken samples is 10 out of 13 Syariah Commercial Bank in Indonesia. The research result showed that zakat, qardh, and murabahah does not affect the Syariah Commercial Bank financial performance. Mudharabah and corporate social responsibility (CSR) showed significant negative influence towards Syariah Commercial Bank financial performance, while musyarakah affects significantly positive toward Syariah Commercial Bank financial performance in Indonesia.